2008
DOI: 10.1149/1.2806030
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Metal Barrier with Porous Methyl Silsesquioxane Films

Abstract: Integration of porous ultralow-dielectrics into advanced copper interconnect scheme has been a challenge. Among other issues, metal diffusion/drift into interconnected pores consequently leading to the degradation of dielectrics is a concern. In the present work, the electrical stability of the metal-insulator-semiconductor ͑MIS͒ capacitors with various metal electrodes on porous methyl silsesquioxane ͑MSQ͒ on thermal oxide/n-type silicon was investigated. Our results suggest that the tendency of various metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In contrast, for the Cu/MnSiO 3 /SiO 2 sample, there are no measurable changes in the CV profile following the atmosphere anneal at 300 °C. Previous reports have suggested that excess metallic Mn resulting from the incomplete conversion of Mn into MnSiO 3 could diffuse through the deposited Cu film to the surface, resulting in the formation of Mn oxide layer thereby preventing Cu oxidation and hence inhibiting Cu diffusion into the dielectric. Thus, in order to ascertain whether the MnSiO 3 barrier at the metal/SiO 2 interface or a surface localized Mn oxide is responsible for the stability of the MnSiO 3 sample, XPS measurements of both samples were performed to determine the surface chemical composition post atmosphere ambient anneal. The survey spectra for both samples, shown in Figure a, reveal that the only elements present in the top surface of the samples are copper, oxygen and traces of adventitious carbon, within XPS detection limits.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, for the Cu/MnSiO 3 /SiO 2 sample, there are no measurable changes in the CV profile following the atmosphere anneal at 300 °C. Previous reports have suggested that excess metallic Mn resulting from the incomplete conversion of Mn into MnSiO 3 could diffuse through the deposited Cu film to the surface, resulting in the formation of Mn oxide layer thereby preventing Cu oxidation and hence inhibiting Cu diffusion into the dielectric. Thus, in order to ascertain whether the MnSiO 3 barrier at the metal/SiO 2 interface or a surface localized Mn oxide is responsible for the stability of the MnSiO 3 sample, XPS measurements of both samples were performed to determine the surface chemical composition post atmosphere ambient anneal. The survey spectra for both samples, shown in Figure a, reveal that the only elements present in the top surface of the samples are copper, oxygen and traces of adventitious carbon, within XPS detection limits.…”
Section: Resultsmentioning
confidence: 99%
“…Since the year of 2000, bismuth film electrodes (BiFE) have been used to replace mercury electrodes 1013 in stripping applications due to their large potential window, low toxicity and no need of deoxygenation procedure during measurement. Bi films are usually prepared by ex situ onto the surface of substrate.…”
Section: The Interference Of Coexistent Metal Ions On the Determinatimentioning
confidence: 99%
“…16 Even at room temperature, a large leakage current has been observed when using Al as an electrode metal in these tests. 17 This instability has been attributed to the drift of Al ions into the dielectric under electric field, 18 that deteriorates the quality of the dielectric. 19 Aluminum ions are believed to form readily at the Al/dielectric interface due to oxidation.…”
Section: H820mentioning
confidence: 99%